“La acción de vicios redhibitorios en el contrato de compraventa y su incidencia en la cosa vendida, en la Unidad Judicial Civil del cantón Riobamba, en el periodo enero 2015 – junio 2015” - Ocaña Ocaña, Jonathan Patricio (2016)
One of the effects arising from the purchase agreement is a possible rescission, if the item of sold possesses hidden demage or latent defects and is determined, as it is ruled by the Civil Code, Article 1797 “rescission action is called that the buyer has for rescinding the sale or the proce proportionally recedd for hidden defects of the sold item, root or cabinet, called crippling”. Given these flaws, the item sold produces a problem the buyer, who expected destine to a daily and practical use, which does not occur because the item sold has lost is natural use, according to the Civil Code, Article 1797 “ crippling defects are those which have the following qualities” being such sold thing for them that does not serve to their natural use, or serve only imperfectly, so that is supposed, the buyer had known it and had not bought it, or had bought at much lower price. Now that it is not always easy to determine whether the natural use of the item sold, is compromised, therefore the Civil Code has allocated a number of requirements to establish latent defects or latent repayable. Finally, it notes the importance that the action of latent defects in the sales contract has because this will cause an impact on the sold item.